Granzyme B in circulating CD8+ T cells as a biomarker of immunotherapy effectiveness and disability in neuromyelitis optica spectrum disorders - Shi, Ziyan; Du, Qin; Wang, Xiaofei; Wang, Jianchen; Chen, Hongxi; Lang, Yanling; Kong, Lingyao; Luo, Wenqin; Yang, Mu; Zhou, Hongyu (Frontiers in Immunology, 2022)
Background and Objective Neuromyelitis optica spectrum disorders (NMOSD) are chronical inflammatory demyelinating diseases of the central nervous system (CNS) and the underlying mechanism remains unclear. Several recent studies have demonstrated that T cells play a pivotal role in the pathogenesis of NMOSD. In this study, we investigated CD8+ T cell phenotypes and levels of the cytotoxic protein granzyme B (GzmB), as well as their potential clinical application in NMOSD. Methods In this study, 90 peripheral blood samples were collected from 59 NMOSD patients with seropositive anti-aquaporin-4 (AQP4) antibodies and 31 sex- and age-matched healthy donors (HDs). Flow cytometry was used to detect circulating levels of GzmB and CD8+ T cell subpopulations, including naïve (TN, CCD7+CD45RA+), central memory (TCM, CCD7+CD45RA-), effector memory (TEM, CCD7-CD45RA-), terminal differentiation effector memory cells (TEMRA, CCD7-CD45RA+) in both groups. The associations between GzmB levels in CD8+T cells and clinical characteristics of NMOSD were evaluated. Results NMOSD patients exhibited significantly decreased proportions of CD8+TN cells and increased proportions of highly differentiated CD8+T cells (TEMRA) compared with HDs. In addition, levels of GzmB in CD8+ T cells were markedly higher in NMOSD patients than in HDs. Moreover, we observed that high proportions of GzmB-expressing CD8+ T cells were more common in patients with a poor response to immunotherapies, and showed a good potential to distinguish poor responders from responders (ACU=0.89). Clinical correlation analysis indicated that high levels of GzmB in CD8+ T cells were not only related to severe disability but also significantly associated with increased serum levels of neurofilament light (NFL) and glial fibrillary acidic protein (GFAP). Multivariate linear regression analyses further suggested that GzmB expression in CD8+ T cells was predominantly associated with disability and immunotherapy effectiveness in NMOSD, independent of the sex, age, and disease phase. Transcription factor T-bet in CD8+ T cells were also significantly elevated in NMOSD and were associated with increasing number of circulating CD8+TEMRA cells and GzmB-expressing CD8+T cells. Conclusions Our study support the involvement of GzmB-expressing CD8+ T cells in the inflammatory response in patients with NMOSD and provide a potential biomarker for disease immunotherapy effectiveness and disability progression.